Development of micronutrient fertilizer strategies for rice yield increase in Sub-Saharan Africa - CGIAR Research Program on Rice (2021)
The yield increases with application of micronutrients proved through experiments in Tanzania. The micronutrients are being tested in Madagascar, Rwanda, Nigeria, Uganda and Senegal through micronutrient omission trails.